Transcranial magnetic stimulation in patients with functional limb weakness. Issue 5 (8th May 2017) - Chen, Benson S; Alan Barber, P; Stinear, Cathy M
Abstract : Objectives: Functional limb weakness can be a protracted and debilitating condition. Most treatment approaches combine behavioural or psychiatric approaches with a motor learning programme. We aimed to determine if transcranial magnetic stimulation (TMS) could confirm the integrity of corticomotor pathways and improve outcome in patients with functional limb weakness. Methods: Patients with functional limb weakness were identified. MRI of the brain and spinal cord were performed to exclude structural lesions. TMS was performed using a figure-of-eight coil connected to a MagStim 200 stimulator. Focal stimulation was delivered over the contralateral primary motor cortex to the paretic limb. Motor evoked potentials (MEPs) were measured using surface electromyography of the first dorsal interosseous and tibialis anterior muscles. Patients were directed to attend to the presence of visible and palpable muscle twitches. A Functional Independence Measure (FIM) score was calculated pre- and post-TMS. Results: Four patients (3 female; mean age (range) 33 (16-48) years) were assessed as having functional limb weakness after neurological and psychiatric assessment. Two patients had previous diagnoses of functional neurologic conditions. TMS was performed 15 (3-34) days after symptom onset and demonstrated the integrity of the corticomotor pathways with normal MEP latency, amplitude and morphology in all patients. There were no complications. The mean (range) FIM score improved from 69 (36-106) pre-TMS to 81 (60 to 116) post-TMS. Two patients returned to normal or near-normal at discharge and one had residual weakness but was independent with activities of daily living (ADLs). One patient had resistant weakness and remained dependent with ADLs. Conclusions: TMS is a safe and well-tolerated tool that has both diagnostic and therapeutic applications in patients with functional limb weakness. It can be used alongside conventional techniques to confirm normal corticomotor physiology and, by generating muscle contractions, enable patients to recognise their own potential for recovery.